Squirrels, Timber, and the ‘Ecological Self’ in Faulkner’s The Bear - Hada, Kenneth E. (Hungarian Journal of English and American Studies, 2021)
Reading William Faulkner’s “The Bear” with a literary ecologist perspective could shift readers from abstraction to ethical responsibility. Deep ecology, ecopsychology, and constructionist views of human development align with ethical criticism and ecocriticism to establish the basis for what Freya Mathews refers to as the “Ecological Self.” Mathews joins others in noting that human development must become ecologically self-aware—a state engendering emotional, ethical responses, confirming wholeness and sustainability rather than mere intellectual, theoretical acknowledgment, or worse, pathological denial. Literary ecology joins textual analysis and meta-textual information to affirm the story’s implied stewardship, despite Faulkner’s sometimes unclear, tragic view of his landscape. An optimistic ecocritical reading affirms, or surpasses, various critical approaches often used with the story—in particular, the paradise myth. Reading ecocritically affirms individual health and sustainability with human culture and nonhuman nature. (KH)